2011
DOI: 10.1002/anie.201103096
|View full text |Cite
|
Sign up to set email alerts
|

Solvation and Stabilization of Metallic Nanoparticles in Ionic Liquids

Abstract: Some room-temperature ionic liquids can hold stable suspensions of nanoparticles without additional surface-active agents [1] through mechanisms of solvation and stabilization that are not understood at present, particularly for metallic nanoparticles. These systems are relevant for applications in catalysis, lubrication, electrochemical devices, and chemical processes. We address this issue by studying the interactions and ordering of ionic liquids around metallic nanoparticles using molecular dynamics simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
148
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(154 citation statements)
references
References 33 publications
6
148
0
Order By: Relevance
“…While many studies have reported on alternating layers of opposite ions near the surfaces [13][14][15][16][17][18][19][20][21][22][23][28][29][30][31][32][33][34][35] it was recently conjectured through a revision of empirical methods 24 that RTILs are not much different from dilute electrolytes. Using spatial dynamics methods, we have demonstrated the nature of decaying charge distributions near the surfaces are in fact enslaved by the bulk and thus, EDLs in RTILs can exhibit both ion layering and a standard decaying behavior as in dilute electrolytes.…”
Section: Discussionmentioning
confidence: 99%
“…While many studies have reported on alternating layers of opposite ions near the surfaces [13][14][15][16][17][18][19][20][21][22][23][28][29][30][31][32][33][34][35] it was recently conjectured through a revision of empirical methods 24 that RTILs are not much different from dilute electrolytes. Using spatial dynamics methods, we have demonstrated the nature of decaying charge distributions near the surfaces are in fact enslaved by the bulk and thus, EDLs in RTILs can exhibit both ion layering and a standard decaying behavior as in dilute electrolytes.…”
Section: Discussionmentioning
confidence: 99%
“…The results from a recent theoretical study on 2 nm model Ru(0) particles in [C 4 C 1 Im][BTA] indicated that transition metal particles are preferentially solvated by the charged moieties of the ions with a one-ion-thick interface layer [34]. In this study by Pensado et al, both types of ions (i.e., anions and cations) were assumed to interact with the metal surface.…”
Section: Effect Of the Il Anionmentioning
confidence: 96%
“…[17] Moreover, metallic nanoparticles in ILs are solvated preferentially by the charged moieties of the ions, with an interface layer that is one ion thick with both cations and anions in close contact with the metal surface. [18] Finally, the presence of water (even in very low concentrations) affects the aggregation of polar and non-polar domains and modulates physicochemical properties such as diffusion and viscosity. [15,19] However, the structural organization and properties of ILs containing diluted solutions ( Figure 3) has received much less attention.…”
Section: Introductionmentioning
confidence: 99%